The Slopes of the Railways of the Moscow as an Ecological Niche for Rare and Endangered Plant Species - Vinogradova, Yulia; Barinov, Andrey; Bochkin, Vassiliy (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The role of the railways slopes as an ecological niche for rare and endangered plant species was reflected on the example of the Moscow metropolis. A comparative analysis of the information from the database on the flora of the railways in Moscow (Barinov, 2017) and data from the Red Book of Moscow (Red Book ..., 2011) was carried out. The database was created on the basis of herbarium materials stored in the Herbarium of the Main Botanical Garden (MHA) and Herbarium of the M.V. Lomonosov Moscow State University (MW). It includes information on 480 natural and 606 alien species. The railways were considered in a broad sense (including railway tracks, platforms, stations, adjacent slopes and cuvettes, exclusion zones). The length of the Moscow railways in the old borders of the city (until 2012) is more than 300 km. 480 aboriginal species was registered on the railway, 34 (7 %) of them are considered as rare species and were included in the ’Red Book of Moscow’. Two species Botrychium lunaria and Allium angulosum have been receive category 0, four Antennaria dioica, Nonea pulla, Dactylorhiza fuchsii, and Thymus marschallianus – category 1. Labels of all herbarium specimens are given. Some railway’s populations of rare species are quite stable. Thus, Allium angulosum on the meadow near the railway station Bojnja, and Thymus marschallianus on the railway embankments with meadow-steppe plant communities in front of Butovo station exist here more than 20 years. The record belonged to Thymus × loevyanus: this hybridogenic taxon grows in the same locality – on the railway embankments with meadow steppe cenoses near the railway station Butovo since 1946 (more than 65 years). Since in Moscow even mosaic meadow communities are extremely rare, it is necessary to use all measures to maintain the remnants these natural phytocenoses, the disappearance of which is the main threat to the reduction of natural biodiversity. The task is to develop measures to preserve indigenous species on the roadside, in spite of the prevailing practice of covering slopes with rolling lawns. The proportion of natural meadow species can be increased with a suitable mode of mowing and abandoning of herbicides and possibly also by artificial seeding of native plants. In a metropolis, such an approach will be the only possible way to increase the ecological significance of roadside habitats that will be able to assume the function of ecological corridors not only for native plants but also insects and even, possibly, animals. It is concluded that in large cities, railway slopes can make up for the lack of suitable habitats for both natural vegetation in general, and for rare and endangered plant species.